Drag the tiles to the correct boxes to complete the pairs,
Match each function with its correct description.
f(x)= (-x + 1)³(x + 2)²(x-3)
f(x) = (x+6)(2x - 3)(x - 1)²
f(x) = (-2x + 1)2(x - 3)²(x + 1)
f(x) = (x - 2)2(-2x - 1)²(x + 1)
The degree of the function is 4,
and the leading coefficient is
positive.
The degree of the function is 5,
and the leading coefficient is
negative.
The degree of the function is 6,
and the leading coefficient is
negative.
The degree of the function is 5,
and the leading coefficient is
positive.